2015
DOI: 10.1007/978-3-662-48350-3_72
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Parameterized Algorithms for Planar Facility Location Problems Using Voronoi Diagrams

Abstract: We study a general family of facility location problems defined on planar graphs and on the 2-dimensional plane. In these problems, a subset of k objects has to be selected, satisfying certain packing (disjointness) and covering constraints. Our main result is showing that, for each of these problems, the n O(k) time brute force algorithm of selecting k objects can be improved to n O( √ k) time. The algorithm is based on an idea that was introduced recently in the design of geometric QPTASs, but was not yet us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
122
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(130 citation statements)
references
References 46 publications
3
122
0
Order By: Relevance
“…We consider the decision version of this problem in which we are given a set P of n colored points in the plane and an integer k, and we want to decide whether or not P has a consistent subset of size k. Moreover, if the answer is positive, then we want to find such a subset. This problem can be solved in time n O(k) by checking all possible subsets of size k. We show how to solve this problem in time n O( √ k) ; we use a recursive separator-based technique that was introduced in 1993 by Hwang et al [7] for the Euclidean k-center problem, and then extended by Marx and Pilipczuk [10] for planar facility location problems. Although this technique is known before, its application in our setting is not straightforward and requires technical details which we give in this section.…”
Section: A Subexponential Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the decision version of this problem in which we are given a set P of n colored points in the plane and an integer k, and we want to decide whether or not P has a consistent subset of size k. Moreover, if the answer is positive, then we want to find such a subset. This problem can be solved in time n O(k) by checking all possible subsets of size k. We show how to solve this problem in time n O( √ k) ; we use a recursive separator-based technique that was introduced in 1993 by Hwang et al [7] for the Euclidean k-center problem, and then extended by Marx and Pilipczuk [10] for planar facility location problems. Although this technique is known before, its application in our setting is not straightforward and requires technical details which we give in this section.…”
Section: A Subexponential Algorithmmentioning
confidence: 99%
“…We introduce a new vertex at infinity and connect these three rays to that vertex. To this end we obtain a 2-connected 3-regular planar graph, namely G. Marx and Pilipczuk [10] showed that such a graph has a polygonal separator δ of size O( √ k) (going through O( √ k) faces and vertices) that is face balanced, in the sense that there are at most 2k/3 faces of G strictly inside δ and at most 2k/3 faces of G strictly outside δ. The vertices of δ alternate between points of S and the vertices of G as depicted in Figure 1(a).…”
Section: A Subexponential Algorithmmentioning
confidence: 99%
“…For example, in unit disk graphs, i.e., intersection graphs of unit-radius disks in the plane, I S , H C , V C can be solved in time 2Õ ( √ n) [1,39,16], and k C can be solved in time 2Õ ( √ nk) for every k [29,3]. All these bounds are essentially tight under the ETH, up to polylogarithmic factors in the exponent.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm is a simple win-win strategy: either we have a vertex of large degree and we branch on choosing it to the solution or not, or all degrees are small and thus there exists a small balanced separator, which allows us for one step of divide & conquer. Recently, Marx and Pilipczuk [39] used a di erent approach to obtain a 2 O( √ n) p O (1) algorithm for I S in string graphs, where p is the number of geometric vertices in the representation.…”
Section: Introductionmentioning
confidence: 99%
“…1{ε q [37]. Therefore, to get an efficient approximation scheme one need to approximate both the number of centers and the cost.…”
Section: Introductionmentioning
confidence: 99%